2020
DOI: 10.1038/s41598-020-73772-z
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-2-macroglobulin from circulating exosome-like vesicles is increased in women with preterm pregnancies

Abstract: Preterm labor (PTL) and Preterm Premature Rupture of Membranes (PPROM) impose substantial morbimortality on mothers and newborns. Exosomes act in intercellular communication carrying molecules involved in physiopathological processes. Little is known about exosomal proteins in prematurity. Our aim was to evaluate the protein expression of hemopexin, C1 inhibitor (C1INH) and alpha-2-macroglobulin (A2M) from circulating exosomes of women with PTL and PPROM. Plasma was obtained from PTL, PPROM, Term in labor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Several studies have reported the EV-mediated secretion of a2M ( 41 43 ). In western blot analysis, a2M was detected both in cell lysate and secreted EVs from BC cells ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the EV-mediated secretion of a2M ( 41 43 ). In western blot analysis, a2M was detected both in cell lysate and secreted EVs from BC cells ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the EV-mediated secretion of a2M (41)(42)(43). In western blot analysis, a2M was detected both 6A).…”
Section: A2m From Bc Is Co-fractionated With Common Ev Markersmentioning
confidence: 94%
“…Western blot was performed to detect the exosome marker CD63; the negative control was cytochrome c (Santa Cruz Biotechnology, Inc.—Texas, USA). This step was performed jointly with another study from our group that has already been published [ 52 ]. Briefly, 4× Laemmli buffer and mercaptoethanol (1:10) were used for protein extraction (5 min at 95 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we measured the particle sizes of PMSC-Exos with nanoparticle tracking analysis (NTA) using ZetaView PMX 110 (Particle Metrix) and its corresponding software ZetaView 8.04.02. PMSC-Exos were diluted in sterile PBS before NTA analysis [ 26 ]. NTA measurement was recorded and analyzed at 11 positions.…”
Section: Methodsmentioning
confidence: 99%